Variable 1.7 M TO 2 M amplifier and fiber laser based on ase suppressed TDFA - Emami S.D.; Lee H.J.; Arabanian A.S. (Nova Science Publishers, Inc., 2023)
Amplifiers (electronic); Fiber lasers; Fibers; Geometry; Low pass filters; Numerical methods; Photonic crystal fibers; Plasma diagnostics; Rare earth-doped fibers; Rare earths; Thulium; Amplified spontaneous emissions; Geometrical structure; Optical low-pass filter; Photonics crystal fibers; TDFA; Thulium doped fiber amplifiers; Thulium-doped fibers; Transmission characteristics; Fiber amplifiers